THU0312 AUTOLOGOUS NON-MYELOABLATIVE HEMATOPOIETIC STEM CELL TRANSPLANTATION FOR REFRACTORY TAKAYASU ARTERITIS: A RETROSPECTIVE MULTICENTRE CASE-SERIES FROM THE AUTOIMMUNE DISEASES WORKING PARTY (ADWP) OF THE EUROPEAN SOCIETY FOR BLOOD AND MARROW TRANSPLANTATION (EBMT). (13th June 2020) - Laurent, C.; Marjanovic, Z.; Henes, J.; Farge, D.; Badoglio, M.; Snowden, J.; Fain, O.; Alexander, T.; Oliveira, M. C.; Mekinian, A.
Abstract : Background: Takayasu arteritis (TAK) is a chronic granulomatous large-vessel vasculitis, characterized by arterial thickening and fibrosis leading to stenosis and vascular occlusions. More than 10-20% of patients are refractory to conventional immunosuppressive therapy. Autologous hematopoietic stem cell transplantation (AHSCT) has emerged as a promising treatment option in severely affected and refractory patients with various autoimmune diseases and vasculitis, particularly ANCA-positive vasculitis and Behçet's disease. Objectives: This study, approved by the ADWP, aims to evaluate the use and outcome of AHSCT in adult TAK patients. Methods: This is a retrospective survey of patients reported to the EBMT registry between 1998 and 2019, who received AHSCT primarily for TAK. Clinical and laboratory data, including data on diagnosis, previous lines of therapy, transplant regimen, treatment-related mortality, as well as data regarding course of disease and treatment were recorded. Results: Data from six adult patients treated with AHSCT between 2003 and 2019 for refractory Takayasu have been identified. Median (ranges) follow-up was 9.9 (1-14) years. Five patients were female (83%), median age was 25 (9-39) years at diagnosis and 28 (22-41) years at HSCT. All patients were pretreated with a median of 6 (4-8) lines of therapy, including systemic steroids (6 patients), methotrexate (5 patients), cyclophosphamide, mycophenolate mofetil or infliximab (4 patients), tocilizumab or etanercept (2 patients), and other biologic or conventional-synthetic DMARDs. Conditioning included cyclophosphamide and rabbit anti-thymocyte globulin in all patients. At six months post-transplantation, remission was obtained in all cases, which persisted at 12 months in 5 cases. Four patients reactivated TAK at a median time of 27 (7-52) months after AHSCT, and 3 resumed disease-modifying therapy. At last follow-up, all patients were alive, 2 patients were in remission (off-therapy), 2 patients improved compared to baseline, and 2 patients were in complete and partial remission, respectively, under immunosuppressive treatment. Conclusion: This small retrospective series demonstrates that AHSCT has the potential to provide significant clinical responses in TAK patients who had been unresponsive to previous immunosuppressive therapy, with an acceptable safety profile. Acknowledgments: no Disclosure of Interests: CHARLOTTE LAURENT: None declared, ZORA MARJANOVIC: None declared, Jörg Henes Grant/research support from: Novartis, Roche-Chugai, Consultant of: Novartis, Roche, Celgene, Pfizer, Abbvie, Sanofi, Boehringer-Ingelheim, , DOMNIQUE FARGE: None declared, MANUELA BADOGLIO: None declared, John SNOWDEN: None declared, olivier fain: None declared, Tobias Alexander: None declared, Maria Carolina Oliveira: None declared, Arsene Mekinian: None declared